Mechanism and inhibition of the papain‐like protease, PLpro, of SARS‐CoV‐2. (26th August 2020) - Klemm, Theresa; Ebert, Gregor; Calleja, Dale J; Allison, Cody C; Richardson, Lachlan W; Bernardini, Jonathan P; Lu, Bernadine GC; Kuchel, Nathan W; Grohmann, Christoph; Shibata, Yuri; Gan, Zhong Yan; Cooney, James P; et al.
Abstract: The SARS‐CoV‐2 coronavirus encodes an essential papain‐like protease domain as part of its non‐structural protein (nsp)‐3, namely SARS2 PLpro, that cleaves the viral polyprotein, but also removes ubiquitin‐like ISG15 protein modifications as well as, with lower activity, Lys48‐linked polyubiquitin. Structures of PLpro bound to ubiquitin and ISG15 reveal that the S1 ubiquitin‐binding site is responsible for high ISG15 activity, while the S2 binding site provides Lys48 chain specificity and cleavage efficiency. To identify PLpro inhibitors in a repurposing approach, screening of 3, 727 unique approved drugs and clinical compounds against SARS2 PLpro identified no compounds that inhibited PLpro consistently or that could be validated in counterscreens. More promisingly, non‐covalent small molecule SARS PLpro inhibitors also target SARS2 PLpro, prevent self‐processing of nsp3 in cells and display high potency and excellent antiviral activity in a SARS‐CoV‐2 infection model. Synopsis: Crystal structures explain the specificity of SARS‐CoV‐2 papain‐like protease, PLpro, for ISG15 and Lys48‐linked diubiquitin, and specific inhibition of PLpro by small molecules, shows strong antiviral effects. SARS‐CoV-2 PLpro preferentially cleaves ISG15 and also targets longer Lys48‐linked ubiquitin chains. Preference for ISG15 is provided by the S1 ubiquitin binding site in PLpro, while Lys48‐polyubiquitin specificity is provided by the S2 ubiquitin binding site. In a high‐throughput screen, FDA approved drugs and late stage clinical compounds are unable to inhibit PLpro in vitro . Known SARS PLpro inhibitors also target SARS2 PLpro and show anti‐viral efficacy. Abstract : Crystal structure and biochemical analysis explains the specificity of SARS‐CoV‐2 PLpro for ISG15 and longer Lys48‐linked ubiquitin chains leading to the identification of inhibitors that show promising antiviral activity in a SARS‐CoV‐2 infection model.